A new species of Oecanthus and Oecanthus lineolatus Saussure, 1897 from Southern Brazil: species description, including phallic sclerites, metanotal glands and calling song (Orthoptera: Gryllidae: Oecanthinae) - Zefa, Edison; Neutzling, Alexandre Schneid; Redü, Darlan Rutz; de Oliveira, Gabriel Lobregat; de Pinho Martins, Luciano (Zootaxa, 2012)
We characterized and compared taxonomic features of two species of tree crickets Oecanthus in tobacco plantation and adja-cent native trees and bushes at Southern Brazil. The marked differences between species included Oecanthus n. sp. with pale-green body, pale-yellow head, greenish-white eyes, file teeth number 32.8±1.2 (31–34, n = 6) and hindwings caudate. Oecan-thus lineolatus is slightly darker as pale-green, with pale-green head, yellow eyes, hind femur variegated with translucent andpale-green, file teeth number 47±2.2 (42–51, n = 18) and hindwings non caudate. Both species also differ in calling song dominant frequency and temporal parameters, as well as in the morphology of metanotal gland.